A study of performance indicators and Ofsted ratings in English child protection services. (August 2016) - Hood, Rick; Grant, Robert; Jones, Ray; Goldacre, Allie
Abstract: This paper presents new findings from a study of performance measures for children in need and child protection services in England. National datasets and census returns from 152 local authorities over a 13-year period were combined in order to analyse trends and correlations in quality indicators. The study also explored the relationship between these measures and inspection ratings from the Office for Standards in Education, Children's Services and Skills (Ofsted), with a particular focus on services rated as inadequate. The available quality measures mainly focused on the timeliness of work processes, but these did not seem to affect outcomes in the form of re-referral rates. However, re-referrals were higher in local authorities with a tendency to close cases quickly and in those with high rates of agency workers. A small number of indicators were able to predict an inadequate Ofsted rating in 2012 and 2013. Changes in performance measures in the year following an inadequate Ofsted rating may suggest greater use of protective interventions compared with similarly performing local authorities. Implications are considered for performance measurement, management and inspection in the field of child protection. Highlights: Quality measures mainly focused on the timeliness of work processes, but these did not seem to affect outcomes in the form of re-referral rates. Re-referrals, which are a negative outcomes measure, were higher in local authorities with a tendency to close cases quickly and in those with high rates of agency workers. A small number of indicators were often enough to predict an inadequate Ofsted rating. In the year following an inadequate Ofsted rating, services seemed to make greater use of child protection interventions. Aspects of the Ofsted inspection process may be exacerbating the shift towards protective interventions in the sector as a whole.